Relative Contribution of Different Potentials in the Estimation of Directed Flow - Sharma, Ankita (My University, 2012)
The present work deals with the theoretical study of directed flow in heavy ion collisions at intermediate energies. We present a complete systematic study of directed flow for asymmetric colliding nuclei for heavy ion reactions in the energy range between 60 ( ) and 140 by using hard equation of state. This study is performed within an isospin-dependent quantum molecular dynamics (IQMD) model. We envision an interesting outcome for asymmetric colliding nuclei. Also the effect of different potentials on heavy ion collisions has been studied.
Keywords: directed flow